Social security as Markov equilibrium in OLG models: A note - Gonzalez Eiras, Martín (2011)
I refine and extend the Markov perfect equilibrium of the social security policy game in Forni (2005) for the special case of logarithmic utility. Under the restriction that the policy function be continuous, instead of differentiable, the equilibrium is globally well defined and its dynamics always stable.